Rho-kinase 2選択的阻害剤は日本人統合失調症患者で見つかったArhgap10遺伝子バリアントを有するマウスの内側前頭前皮質のスパイン密度低下を改善する - 朱, 文俊; 田中, 里奈子; 貝淵, 弘三; 森, 大輔; 毛利, 彰宏; 橘, 大輝; 溝口, 博之; 山田, 清文; 永井, 拓; 尾崎, 紀夫; 鍋島, 俊隆; 小林, 洋平 (日本薬理学会年会要旨集, 2023)
Copy number variants in the ARHGAP10 gene are associated with schizophrenia (SCZ). We have previously demonstrated that Rho-kinase (ROCK) inhibitor, fasudil, ameliorates the decreased spine density in the medial prefrontal cortex (mPFC) of Arhgap10 S490P/NHEJ mice carrying the variants that mimic the ARHGAP10 variants found in a Japanese SCZ patient. Accordingly, we have proposed that ROCK is a potentially novel therapeutic target in SCZ. It is well known that there are two subtypes of ROCK, ROCK1 and ROCK2, and that fasudil inhibits both subtypes. Since ROCK2 is highly expressed in the brain, here we evaluated the effect of a selective ROCK2 inhibitor, belumosudil (KD025), on spine density in Arhgap10 S490P/NHEJ mice. We measured the spine density of pyramidal neurons in layer 2/3 of the mPFC in Arhgap10 S490P/NHEJ mice following daily oral administration of KD025 for one week. Moreover, we evaluated the general behaviors in an open field and systolic blood pressure after KD025 treatment. KD025 ameliorated decreased spine density of cortical neurons in the mPFC of Arhgap10 S490P/NHEJ mice, but had little effects on general behaviors and systolic blood pressure induced by fasudil. These observations suggest that ROCK2 is a more appropriate therapeutic target in SCZ, with little inducibility of hypotension.